Diagnostic approaches and potential therapeutic options for coronavirus disease (COVID-19) (2020)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged in Wuhan city of China in late December 2019 and identified as a novel coronavirus. Due to its contagious nature, the virus spreads rapidly and causes coronavirus disease 2019 (COVID-19). The global tally of COVID-19 spikes 28 million. The fears and stress associated with SARS- CoV-2 demolished the socio-economic status all over the world. Researchers are trying around the clock to find out the treatment especially antiviral drugs and/or vaccines that could potentially control the viral spread and manage the ongoing unprecedented global crises. To date, more than 300 clinical trials have been conducted on various antiviral drugs, and immunomodulators are being evaluated at various stages of COVID-19. This review is aimed to collect and summarize a list of drugs used to treat COVID-19 for instance, dexamethasone, chloroquine, hydroxychloroquine, lopinavir/ritonavir, favipiravir, remdesivir, tociluzimab, nitazoxanide, and ivermectin. However, some of these drugs are not effective and suspended by the WHO (World Health Organization).